Ethnicity and Scale in Pastoral-Sedentary Relations: Early Barth and his relevance to Sudan.1 - M. Ahmed, Abdel Ghaffar (IJRDO - Journal of Social Science and Humanities Research, 2017)
This paper addresses issues of ethnicity and scale, two major areas in Fredrik Barth’s analysis of society. It specifically relates to Barth’s “general perspective on nomad-sedentary relations in the Middle East” where two approaches are possible. Pastoral groups can be either depicted through their relation to their total environment or they can be explicitly viewed from a symbiotic relation to the rest of their society. The latter view implies starting with households in rural areas, especially of pastoral groups, showing their symbiotic relations to villages and larger urban settings that represent the environment in which they practice their activities. It identifies the distinct roles of everyone involved and the mediating role of traditional elites and state agents in this process. The space on which theycompete is land where laws have changed in the last few decades. Actors and/or groups of actors use different means to substantiate their claims over the space at hand. History, traditions and laws are invoked to justify the rights to ownership and control of land and other resources. Ethnicity and scale became crucial factors in defining the roles of different agents. Changes have taken place and newly adopted technology had its influence on relations of different pastoral and sedentary groups even when they are in remote areas far away from the center for decision making in the state. These new elements have their impact on ethnicity and scale and examples from pastoralists and settled people in Sudan shall illustrate this point.